Achievement Motivation and Academic Procrastination: a Correlation Studies - Novirson, Rizki; Lubis, Khadijah (Department of Guidance and Counseling, FIP, Undiksha, 2020)
This research is based on the phenomenon that found in school, there are many students who carry out academic procrastination. This study examines the correlation about achievement motivation and academic procrastination behavior in students. Correlational design is a type of research that is used, collecting data from 270 students using with questionnaire. Finally will be seen an overview of the level of achievement motivation and academic procrastination, and the relationship of both.